EU-India relations in the multi-vector matrix of science diplomacy and Asia-Europe Meeting - Zane Šime (Research in Globalization, 2021)
Online training events deserve more attention as a form of people-to-people connectivity. The purpose of the article is to elaborate on how online training events gain prominence in the context of the COVID-19 imposed restrictions on geographical mobility. The autoethnographic account provides new ideas on what higher education extra-curricular and capacity building activities should be taken into consideration when taking a comprehensive look at people-to-people sustainable connectivity. As the analysed three online training events that took place over the summer 2020 show, these virtual occasions of people-to-people connectivity are promising building blocks for the future exploration of the EU structural diplomacy towards India both in a bilateral setting and multilateral context of Asia-Europe Meeting.
Keywords: 330; Structural diplomacy; People-to-people diplomacy; Science diplomacy; EU-India relations; Asia-Europe Meeting